Consumption pattern and determinants of household dietary diversity through farming systems approach - K J, RAGHAVENDRA; D, JACOB; RAJENDRAN, T; PRUSTY, A K; ANSARI, M A; NIRMAL; PUNIA, P; RAVISANKAR, N; SHAMIM, M; SINGH, RAGHUVEER; SATEESHKUMAR, N; NATARAJAN, S K; et al. (The Indian Journal of Agricultural Sciences, 2025)
Integrated Farming Systems (IFS) is a sustainable agricultural model integrating enterprises such as crops, livestock, fisheries, poultry and agroforestry. This model aims to maximize resource use efficiency, boost productivity, diversify income sources and reduce environmental impacts. By promoting the cultivation of diverse crops and rearing of livestock, this IFS model enables farm households to access a wide range of dietary options. This diversity contributes to improved nutrition, fostering balanced diets and enhancing human well-being. The present stury was carried out during 2022–23 to examine IFS interventions under state schemes in Kerala and Tamil Nadu, collecting 412 sample observations through simple random sampling. Dietary Diversity Scores (DDS) and their determinants were analyzed using multinomial logit regression. The results identified four dominant farming systems, viz. crop-based, vegetable- based, livestock-based, and fisheries-based, with livestock-based systems achieving the highest DDS. Conversely, low DDS groups had significantly lower consumption of meat, fruits, and fish. Factors such as education, intercropping, crop rotation, and net income positively influenced dietary diversity, favouring higher DDS. The study underscores the critical role of intercropping and crop rotation in enhancing dietary diversity and recommends policymakers focus on their widespread adoption. Additionally, improving livestock systems is essential to ensure better access to diverse food groups for farm households.